ANALISIS FAKTOR TINGKAT LOYALITAS PELANGGAN TERHADAP MEREK BERNARDI - Ni Made Laksmi Oktavia (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2021)
This thesis discusses the influence of brand communication and brand image on brand loyalty through brand trust as a mediating variable on the Bernardi brand in Surabaya and Sidoarjo. The sample in this study were consumers who had used the Bernardi brand through a questionnaire distributed using the g-form. This research is a quantitative research with the analytical technique used is PLS.)